Return, Risk, and Yield: Evidence from Ex Ante Data - ANG, JAMES S.; PETERSON, DAVID R. (Journal of Finance, 1985)
ABSTRACT The purpose of this study is to investigate the relationship between return and yield in the context of ex ante data from The Value Line Investment Survey and by examining the role of dividends as a proxy for risk. The use of ex ante data should substantially reduce the confounding of tax and information effects that has affected earlier studies. Heteroscedasticity is detected in the after‐tax CAPM and found to be negatively related to yield and positively related to beta. Maximum likelihood methods are used to correct for heteroscedasticity and generate efficient coefficient estimates. Using data for each of the years 1973 through 1983, there is an overall positive relationship between expected return and yield. However, coefficient estimates of yield are highly variable from year to year.